The Change of Thaiyung Language: https://doi.org/10.69692/SUJMRD080201 - Amphatip, Khampa; Meksavanh, Somchay; Thoummavong, Toulaphone; Chandalad, Sivath (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
This research is to study the change of Thaiyung language, particularly the change of words in Yang language that use in the three generation. There are 400 w0rds are used to test the three generation at Namfa village, Viengphouka district, Luangnamtha province. There are 30 samples such as over 70 years old generation, 35-55 years old generation and 15-25 years old generation. The research is used linguistic separation use and linguistic voice translation criteria of words that use by three generations. The result found out that, there are three types of the same words used by three generations. There are four types of the same words used by two generations and there is a type of the different words used by three generations. The language used by three generations still use a lots of Yang words for communication. The first generation use Yang word (A) more than second and third generations. The second and third generations used Yang words with other words in social more than the first generation. And the third generation use other words (B) more than the first and second generations. This is because the third generation of teenagers is open and ready to accept new things all the time and prefer to use the national language (standard Lao language) to communicate with other ethnic groups in society. As a result, the use of the Yang language has diminished in daily life, or may have been used only when living with parents, families, and in a group of people who use the Yang language.